(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Icebreakers are a great way to break the ice, get to know each other better, and create a positive and engaging environment. Whether we are in a professional setting, a social event, or even an online meeting, taking a few minutes to connect and have some fun can greatly enhance our overall experience. Icebreaker activities can help us relax, build rapport, and encourage open communication. They provide an opportunity for everyone to share a little bit about themselves, their interests, and experiences. By participating in these activities, we can develop a sense of camaraderie and build connections with people we may not have interacted with before. During these icebreaker activities, we will be engaging in various games, exercises, or conversations that are designed to break down barriers, foster teamwork, and create a positive and inclusive space for everyone. The activities may involve sharing personal experiences, playing icebreaker games, or working in small groups to solve challenges.